Simulation of Activity Coefficient System Ternary in Acetone Buthanol Ethanol with Uniquac Equation - Sari Ni Ketut; Dira Ernawati (Prosiding International conference on Information Technology and Business (ICITB), 2017)
Simulation of activity coefficients ternary systems using matlab programming language, which results in the appearance of the graph using a spreadsheet tool, less effective and efficient, so it is necessary for the visualization of object-oriented programming language, in addition to easy to be developed at a time when that will come, it has other benefits, in a device project software can use a variety of programming language that supports object-oriented programming, such as C#.Net and VB.Net. This research aims to display the batch distillation simulation of visual binary systems using object-oriented programming. Ethanol buthanol ethanol non azeotropic ternary system, simulation of activity coefficients with rigorous method using a model Differential-Algebraic-Equations (DAEs), where the completion of the model using the language C#.Net, the basic concepts of object-oriented programming consists of classes, objects, abstraction, encapsulation, polymorphism. Antoine parameter data and activity coefficients derived from experimental data. Dimension less time and pressure are set constant, while the variable composition liquida. Profile of liquida composition and vapor composition function dimensionless can be displayed directly from the desktop, to have the non azeotropic ternary system value profile activity coefficient is not equal to one, while the ternary system non azeotropic approaching one. Profile of liquida composition and vapor composition maximum from ternary system non azeotropic is 0.98, while for the ternary system non aeotropic approaching one. Economically using C#.Net language faster, time efficiency and better performance profile. Keywords: Activity coefficients, C#.Net, DAEs, rigorous method, ternary systems